Cell wall chemistry and tissue structure underlie shifts in material properties of a perennial kelp. Issue 3 (3rd July 2018) - Starko, Samuel; Mansfield, Shawn D.; Martone, Patrick T.
ABSTRACT: Laminaria is an abundant kelp genus in temperate nearshore ecosystems that grows with a circannual 'stop-start' pattern. Species of Laminaria play important ecological roles in kelp forests worldwide and are harvested commercially as a source of food and valuable extracts. In order to evaluate seasonal differences in tissue properties and composition, we compared the material properties, histology and cell-wall composition of overwintering blades with newly synthesized, actively growing blades from Laminaria setchellii . We found that overwintering blades were fortified with a thicker cortex and increased cell wall investment, leading to increased material strength. Overwintering tissues were composed of higher proportions of cellulose and fucose-containing polysaccharides (i.e. FCSPs, fucoidans) than newly formed blades and were found to possess thicker cell walls, likely to withstand the waves of winter storms. Chemical cell wall profiling revealed that significant proportions of fucose were associated with cellulose, especially in overwintering tissues, confirming the association between cellulose and some fucose-containing polysaccharides. Changes in material properties during the resting phase may allow these kelps to retain their non-growing blades through several months of winter storms. The results of this study demonstrate how one species might regulate its material properties seasonally, and at the same time shed light on the mechanisms that might control the material properties of kelps in general.